Washingtonia robusta: Mexican Fan Palm - Timothy K. Broschat (EDIS)
The Mexican fan palm is a fast-growing species that can reach heights of 70 to 100 feet, making it too tall for typical residential landscapes. It is native to northern Mexico but grows well in Florida, being hardy down to about 20°F or USDA hardiness zone 9A. Mexican fan palms grow well in a wide range of soils in Florida, but do require good drainage. Though considered a desert palm, it is native to areas having permanent surface or subsurface water and thus is not as drought tolerant as might be expected. This 5-page fact sheet was written by Timothy K. Broschat, and published by the UF Department of Environmental Horticulture, February 2013. http://edis.ifas.ufl.edu/st670